International Scientific Conference Sport Health & Education - Complementary Approach to Gymnastics, 18-20th of June 2015 in Gdansk (2015)
The aim of the conference is to present recent research results and views on the deteriorating health and physical fitness of children, adolescents and adults as well as to indicate the role of various sports activities, healthy lifestyle and education in efficacy to overcome this phenomenon. The conference will also provide an excellent opportunity to exchange views and knowledge from scientists, coaches, physical education teachers and medical representatives of many European countries on the topics of directions of the development and the importance of the complementary aspect of gymnastics in competitive sports, health and physical education. Thematic workshops of "best practices" directed at each profession will be provided. We hope that this conference will be a stimulus to establish a number of international partnership agreements yielding innovative scientific research projects and practical activities in the areas of sports, health and education.